Melamine Disrupts Acetylcholine-Mediated Neural Information Flow in the Hippocampal CA3–CA1 Pathway - Sun, Wei; Liu, Peidong; Tang, Chunzhi; An, Lei (Frontiers in Behavioral Neuroscience, 2021)
Considering the cognitive and synaptic deficits following intragastric administration of melamine, the aim of current investigation was to test if the hippocampal oscillations were affected. The local field potential (LFP) was recorded in the hippocampal CA3-CA1 pathway of Wistar rats during spatial-dependent Y-maze task. General Partial Directed Coherence (gPDC) method was used to assess the directionality of neural information flow between CA3 and CA1 regions. The levels of acetylcholine (ACh) and its esterolytic protease, acetylcholinesterase (AChE), were detected in the hippocampus (HPC) following the behavioral test. The values of phase synchronization between CA3 and CA1 regions in delta, low theta and high theta oscillations were reduced significantly in the melamine-treated group. Moreover, the coupling directional index and the strength of CA3 driving CA1 were critically decreased in the above three frequency bands as well. Meantime, reduction in ACh expression and enhancement in AChE activity were found in the HPC of melamine-treated rats. Intrahippocampal infusion with ACh could mitigate the weakened neural coupling and directional neural information flow (NIF) in parallel with spatial learning improvements. However, infusion of scopolamine, an acetylcholine receptor antagonist, could block the mitigative effects of ACh treatment in melamine rats. These findings provide first evidence that the ACh-mediated neuronal coupling and NIF in the CA3-CA1 pathway are involved in spatial learning deficits induced by chronic melamine exposure.